2016
DOI: 10.1128/aac.02592-15
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Assessment and Pharmacodynamic Implications of Pediatric Cefepime Dosing for Susceptible-Dose-Dependent Organisms

Abstract: The Clinical and Laboratory Standards Institute (CLSI) revised cefepime (CFP) breakpoints for Enterobacteriaceae in 2014, and MICs of 4 and 8 g/ml were reclassified as susceptible-dose dependent (SDD). Pediatric dosing to provide therapeutic concentrations against SDD organisms has not been defined. CFP pharmacokinetics (PK) data from published pediatric studies were analyzed. Population PK parameters were determined using NONMEM, and Monte Carlo simulation was performed to determine an appropriate CFP dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 32 publications
5
38
2
Order By: Relevance
“…In this study, the mean cefepime CL to neonates was 0.18 (0.13-0.24) l/h/kg. Previous reports showed that cefepime CL in neonates was approximately 0.07 to 0.20 l/h/kg (Capparelli et al, 2005;Lima-Rogel et al, 2008;Shoji et al, 2016). Thus, our results were consistent well with former research.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, the mean cefepime CL to neonates was 0.18 (0.13-0.24) l/h/kg. Previous reports showed that cefepime CL in neonates was approximately 0.07 to 0.20 l/h/kg (Capparelli et al, 2005;Lima-Rogel et al, 2008;Shoji et al, 2016). Thus, our results were consistent well with former research.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the function and maturation of the kidneys affects cefepime performance; the pharmacokinetics of neonates differ from those of adults and older children (Reed et al, 1997;Blumer et al, 2001). To the best of our knowledge, pharmacokinetic studies of cefepime has only been conducted in preterm neonates with narrow age range and the developed population pharmacokinetic models had not been externally validated (Capparelli et al, 2005;Lima-Rogel et al, 2008;Shoji et al, 2016). In addition, the developmental pharmacokineticpharmacodynamic based dosing recommendation of cefepime was not available in China.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, every 12-hour regimens of cefepime remain common in tertiary dosing references despite questionable pharmacokinetic and pharmacodynamic optimization. 26 Tobramycin orders were significantly more appropriate when ordered through the electronic antibiotic order set versus a blank order sheet, which could indicate less prescriber familiarity despite similarity in dosing to gentamicin.…”
Section: Discussionmentioning
confidence: 96%
“…11 For organisms with higher MICs of 4 to 8 mg/L, Shoji et al and Lima-Rogel et al both recommended a dose of approximately 50 mg/kg per dose to ensure serum concentrations above the MIC for 60% of the dosing interval. 11,12 For inherently resistant pathogens, such as P. aeruginosa, or difficult to treat infections, such as meningitis, some references suggest higher dosing (50 mg/kg per dose) should be utilized. [6][7][8] This recommendation is consistent with the results and conclusions of the studies presented, corroborated by current CLSI breakpoints of 8 mg/L for Pseudomonas and non-Enterobacteriaceae species and 2 mg/mL for Enterobacteriaceae species.…”
Section: Discussionmentioning
confidence: 99%
“…In the Monte Carlo simulation, preterm neonatal patients (<36 weeks of GA) receiving cefepime doses of 30 to 50 mg/kg every 12 hours attained a time above an MIC of 8 for 60% of the dosing interval with both doses in more than 94% of the population. 12 In term infants, neonates less than 30 days of age, time above MIC for 60% of the dosing interval was achieved in 86.4 and 95.3% of infants with doses of 30 and 50 mg/kg, respectively, every 12 hours. Even when the target attainment rates increased to 70% of time above MIC, this was achieved in 90% of term neonates and 96% of preterm neonates.…”
Section: Literature Review Pharmacokinetic Evaluationmentioning
confidence: 96%